Worthy of debate: discursive coherence and agreement in the formation of the field of sustainability in higher education. (5th June 2019) - Augustine, Grace; King, Brayden G
Abstract: This article explores the development of shared understanding in the field of environmental sustainability in higher education—a field that began with social movement pressure surrounding contentious issues and evolved over decades into a settled field. The study defines and traces two distinct elements of shared understanding in this field: discursive coherence and discursive agreement. Discursive coherence is a shared understanding of which issues matter to a field. Discursive agreement concerns how much agreement there is among field actors regarding those issues. To trace these indicators, we utilize topic modeling alongside qualitative coding of a sample of messages from an online forum of conversations focused on the nascent field. We find that discursive coherence increases over time, but that coherent issues are also more likely to exhibit disagreement, indicating that more coherent issues are seen as more consequential, and therefore more 'worthy of debate' in the nascent field.